Perancangan Dan Pengembangan Sistem Informasi Warung Rongsok Menggunakan Teori 3R (Reduce, Reuse, Recycle) Berbasis Web - Apsyah Paradila; Muhammad Feizal (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Garbage is an item that is no longer used and discarded, so that the item cannot be completely decomposed naturally which will eventually cause environmental damage. So that waste requires special needs in its management, the lack of waste processing containers in RT 01 Pondok Aren makes residents throw garbage carelessly. Because of these problems, a web-based waste processing container was created, this system is called rongsok stall which is a waste saving management application. This thrift shop information system can become a container for waste management with integrity because it is based on the 3R Theory (Reduce, Reuse, Recycle) where this theory is used as a reference standard in processing waste properly and correctly in various developed countries. With the existence of a web-based Warung Rongsok information system, residents can have an effective waste management container that can turn waste into nominal waste savings. And for third parties, you can order trash cans at Warung Rongsok to make it easier to find the trash you want for trash crafts, you can get them easily and quickly. The development methodology used in making this system is a prototype development method and testing is carried out using the blackbox test method and a questionnaire.